ISLAMIC SCHOOL CULTURE AND THE FORMATION OF STUDENTS RELIGIOUS CHARACTER: INSIGHTS FROM SMAN 2 TANGGUL - Siti Fadilah Aini; Akhmad Munir (Program Studi Pendidikan Agama Islam, 2026)
The rapid development of globalization has brought significant changes to students’ ways of thinking and behavior, which in many cases has raised concerns about the weakening of religious values. This condition encourages schools to instill Islamic values through a living and meaningful school culture. This study aims to describe the forms of Islamic school culture, the strategies used in its implementation to foster students’ religious character, as well as the supporting and inhibiting factors at SMAN 2 Tanggul in the 2022/2023 academic year. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model with source and technique triangulation. The findings indicate that Islamic culture at SMAN 2 Tanggul is reflected in the habituation of congregational and dhuha prayers, Qur’an memorization, Islamic holy day commemorations, charitable giving, courteous behavior, and teacher role modeling. The implementation of Islamic culture is carried out through school policies, consistent habituation, and persuasive and humanistic approaches, including principal-led policy-based authority strategies, persuasive strategies through religious activities, and normative-educative strategies through teacher exemplification. The implementation is supported by the active involvement of all school members, the availability of human resources and facilities, and the presence of a school mosque, while obstacles arise from the diverse backgrounds of school members and teachers’ limited capacity to address students’ substantive issues, particularly in character development.